The water-climatic balance of the potato crop during the spring and autumn seasons in the district of Mahmudiya - Radi, Tania Juma; Al-Jaghifi, Abdul Salam Muhammad Mail (Al-Adab Journal, 2021)
The spring and autumn potato crop requires sufficient water to sustain its growth naturally and not to have problems in its growth, so the research focused on calculating the climatic water balance to know the amount of surplus and water deficit for the crop, and accordingly the research concluded that the climatic water balance in all months of the growing season of the potato crop was recorded Water deficit, the crop recorded during the spring lug a very large total water deficit amounting to (-539.1, -638.6, -498.2 mm) for the stations of Hilla, Baghdad and Aziziyah, respectively, as well as for the autumn lug, where the water deficit reached (-561.8, -695.4) , -373 mm) for the stations of the study area, respectively, and this water deficit requires a perfusion process to compensate for the water deficit.